VES Geoelectrical Method for Identification of Aquifer Depth in Coastal Area of North Lombok Regency, Indonesia: Implications for the Sustainable Utilization of Water Resources - Haerul Anwar; Arif Wijaya; Faisal Faisal; Shakal Khan Korai; Imran Tarique; Punhoon Khan Korai (CV FOUNDAE, 2023)
Measurement of the resistivity value distribution of subsurface rocks has been carried out in Mumbul Sari Village, Bayan District, North Lombok, which is one of the drought-prone areas in NTB Province, Indonesia. This research was conducted to identify the presence of groundwater aquifer layers in the study area based on the distribution of resistivity values. Data collection was carried out at two measurement points, namely the MBLS-1 Point with a track length of 700 m and the MBLS-2 Point with a length of 750 m. Data processing was carried out using IP2WIN Software to obtain a one-dimensional subsurface cross-sectional model, then interpreted using a resistivity log to make it easier to draw information on the subsurface point of measurement. Based on the distribution of resistivity values, it is known that the geological layers in the study area consist of pumice tuff, silty silt, sandy silt, and lava. The inversion results from the IP2WIN software show that the depth of the aquifer zone at Point MBLS-1 is 15.6 – 70.2 m with a resistivity value of 90.3 Ωm and a thickness of 54.5 m, while at Point MBLS-2 it is located at a depth of 21.9 – 86.1 m with a resistivity value of 112 Ωm and a thickness 64.3m. The aquifer zone at both measurement points is interpreted as a sandy silt layer. Groundwater drilling is recommended at the MBLS-1 point to a depth of 70 m and at the MBLS-2 point to a depth of 86 m. The geological structure that forms the boundary of the aquifer zone is a layer of compact and hard lava, so for groundwater utilization in the study area, it is recommended to use drilled wells to a depth of 70 – 86 m which is the lower limit of the aquifer layer.